2016
DOI: 10.1186/s40659-016-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA AFAP1-AS1 facilitates tumor growth and promotes metastasis in colorectal cancer

Abstract: Background and objectiveLong non-coding RNAs can regulate tumorigenesis of various cancers. Dys-regulation of lncRNA-AFAP1-AS1 has not been studied in colorectal carcinoma (CRC). This study was to examine the function involvement of AFAP1-AS1 in tumor growth and metastasis of CRC.MethodsRelative expression of AFAP1-AS1 in CRC tissues and CRC cells lines was determined using quantitative real-time PCR (qRT-PCR). Functional involvement of AFAP1-AS1 in tumor proliferation and metastasis was evaluated in AFAP1-AS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…It is well known that aberrant MMP-2 and MMP-9 expression was involved in metastasis [28]. As we expected, the findings of our study showed that AFAP1-AS1 silencing resulted in a significant decrease in cell migration and invasion with downregulation of MMP-2 and MMP-9, which was consistent with others reports [23, 29]. …”
Section: Discussionsupporting
confidence: 83%
“…It is well known that aberrant MMP-2 and MMP-9 expression was involved in metastasis [28]. As we expected, the findings of our study showed that AFAP1-AS1 silencing resulted in a significant decrease in cell migration and invasion with downregulation of MMP-2 and MMP-9, which was consistent with others reports [23, 29]. …”
Section: Discussionsupporting
confidence: 83%
“…After siRNA-mediated silencing of LINC00673 , we found that could significantly inhibit TSCC cancer cell invasive and migratory abilities. In recent findings, some lncRNAs, such as actin filament associated protein 1 antisense RNA1 ( AFAP1-AS1 ) [44, 45], HOX transcript antisense RNA ( HOTAIR ) [46], growth-arrest-specific transcript 5 ( GAS5 ) [47], have been reported to regulate cancer metastasis process by multiple ways. The potential role of LINC00673 abnormalities in TSCC is worth for further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…30,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In this review, the related clinicopathological characteristics and molecular functions of this lncRNA in cancers are presented in Tables 1 and 2.…”
Section: Identification Of Afap1-as1mentioning
confidence: 99%